تعديل الروابط البيتومينية المستخدمة في محافظة اللاذقية باستخدام غبار معامل الرخام. - سلطان بسام; حسن رهام (Latakia University Journal -Engineering Sciences Series, 2019)
The possibilities of modifying Bitumen binder by marble dust are the main objective of this paper. The affected of modifying bitumen is to improve the performance of the Asphalt mixture. The laboratory Experimental program includes the uses of the (60-70) Bitumen and the marble dust, which produces from the cutting of marble stones. The percentage of marble adding are (5-10-15-20) % from bitumen Wight. The experimental programs were conducted to specify the bitumen properties and compare them with the unmodified bitumen. The Experimental results showed that the 15% was optimal. The penetration of the bitumen was (48.3 dcm), which indicate the type of bitumen (40-50). The decrease of the primary penetration is 28.34% and the penetration index is (ip=+0.35), which is lower than the limit (+1). يهدف البحث إلى دراسة إمكانية تعديل الرابط البيتوميني باستخدام غبار معامل الرخام، وذلك لتحسين أداءه. والذي أظهرت أبحاث عديدة حول العالم على جدوى استخدامه. شمل البرنامج الاختباري لهذا البحث استخدام بيتومين (60-70) وغبار رخام ناتج من مخلفات القص والنشر لحجر الرخام المستخدم في المعامل السورية، وقد تمت الإضافات على الرابط البيتوميني بنسب (5-10-15-20)% من وزن البيتومين، وأجريت مجموعة من التجارب لتحديد خواص البيتومين غير المعدل والبيتومين المعدل باستخدام غبار الرخام. بينت التجارب أن نسبة الإضافة (15%) تعد نسبة مثالية للتعديل بنفايات الرخام Marbale Waste حيث يكون عندها الغرز بقيمة (48.3 dcm) أي ضمن الصنف (40-50)، وبنسبة انخفاض عن قيمة الغرز الأولية بنسبة (28.34 %)، ودليل الغرز (IP= +035) في الحالة الموجبة وأقل من الحد المسموح به لدليل الغرز (+1).